Measure of function in rheumatoid arthritis: individualised or classical scales?. Issue 01 (2nd April 2009) - Seror, R; Tubach, F; Baron, G; Guillemin, F; Ravaud, P
Abstract : Background: The Health Assessment Questionnaire Disability Index (HAQ-DI) is the most widely used measure of function in rheumatoid arthritis (RA). Objective: To evaluate individualised forms of the HAQ-DI and thus enhance the incorporation of patients' views in outcome assessment. Patients and methods: HAQ-DI data were prospectively obtained from 370 outpatients with RA treated with leflunomide over a 6-month period. At baseline and final visits, patients had to rate the importance they attached to each activity addressed by the 20 HAQ-DI items, and to select the five activities they considered the most important. Different individualised scales were evaluated: scales preserving all domains, in which the score for each item is multiplied by or added to its importance; and scales involving, for each patient, only the five most important items. The psychometric properties of these scales were compared with those of the HAQ-DI. Results: For each HAQ-DI item, severity and importance scores were weakly correlated. Scores for all individualised scales were highly correlated with the HAQ-DI score (rs >0.75). All scales had a good internal consistency (Cronbach's α 0.87–0.88). Compared with the HAQ-DI, individualised scales did not have better sensitivity to change (standardised response mean 0.64–0.69 vs 0.74). Conclusion: Individualised scales have similar properties to the HAQ-DI. However, individualised questionnaires measuring importance gave complementary information to the measure of disability. Individualisation is probably not needed for group assessment in all randomised controlled trials but, the use of individualised questionnaires may be clinically relevant for individual patients with RA.